The anti-oxidant and pro-oxidant dichotomy of Bcl-2. - Yee, Y.; Chong, S.; Pervaiz, Shazib (2016)
Across a wide spectrum of cellular redox status, there emerges a dichotomy of responses in terms of cell survival/proliferation and cell death. Of note, there is emerging evidence that the anti-apoptotic protein, Bcl-2, in addition to its conventional activity of titrating the pro-apoptotic effects of proteins such as Bax and Bak at the mitochondria, also impacts cell fate decisions via modulating cellular redox metabolism. In this regard, both pro- and anti-oxidant effects of Bcl-2 overexpression have been described under different conditions and cellular contexts. In this short review, we attempt to analyze existing observations and present a probable explanation for the seemingly conflicting redox regulating activity of Bcl-2 from the standpoint of its pro-survival function. The consequential effect(s) of the dual redox functions of Bcl-2 are also discussed, particularly from the viewpoint of developing novel therapeutic strategies against cancers rendered refractory due to the aberrant expression of Bcl-2.